Multifactorial mechanisms of obesity-related HFpEF: the central role of epicardial adipose tissue and therapeutic perspectives - Zhou, Yuxin; Yan, Han; Zhu, Yao; Jiang, Weimin; Zhang, Shujie (Frontiers in Cardiovascular Medicine, 2025)
Heart failure with preserved ejection fraction (HFpEF) accounts for more than half of all heart failure (HF) cases, with its prevalence steadily rising due to population aging, obesity, and the prevalence of metabolic diseases. Obesity, a core risk factor for HFpEF, leads to a distinct clinical phenotype and significantly worsens patient prognosis. Given the limitations of body mass index (BMI) in assessing fat distribution, epicardial adipose tissue (EAT)—a metabolically active fat depot closely adjacent to the myocardium—has emerged as a crucial anatomical and functional bridge linking obesity to HFpEF. Compared to BMI, EAT volume demonstrates a stronger predictive value for diastolic dysfunction and adverse clinical outcomes, highlighting its clinical significance. This review outlines the multifaceted mechanisms through which EAT contributes to HFpEF pathogenesis, including mechanical constraint limiting ventricular diastole, lipid infiltration causing myocardial metabolic disorders, pro-inflammatory factor paracrine secretion inducing fibrosis, microvascular dysfunction, arrhythmogenic effects, and protein modification disorders. Targeting EAT has shown promise in reducing its volume, improving inflammatory status, and enhancing cardiac function. As a pathogenic and therapeutic nexus between obesity and HFpEF, further elucidation of EAT-related mechanisms may facilitate precision diagnosis and intervention for this growing population.